Helminth fauna of domestic waterfowl (goose – Anser anser dom. and duck– Anas platyrhynchos dom.) of Nakhchivan AR - Seyidbeyli, M.; Maharramov, S. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Helminths, causing various diseases, have a negative impact on the quality of meat, egg production, productivity and other characteristics of domestic waterfowl that is an important sourсe of a number of ration components. To prevent the above facts, for the first time from 2014 to 2018, complex helminthological studies were carried out in all regions of the Nakhchivan AR (Babek, Julfa, Sharur, Kengerli, Shahbuz, Ordubad and Sederek) and 359 domestic waterfowl hosts were subjected to complete helminthological autopsy to find 14 helminth species (three species of cestodes – Fimbriaria fasciolaris, Tschertkovilepis setigera, Drepanidotaenia lanceolata, two species of trematodes – Notocotylus attenuatus, Hypoderaeum conoideum and 9 nematode species – Amidostomum anseris, Trichostrongylus tenius, Capillaria obsignata, Ganguleterakis dispar, Tetrameres fissispina, Heterakis gallinarum, Ascaridia galli, Porraceum crassum and Thominx contorta). Of these, 11 species were observed in domestic geese and 12 species in domestic ducks. Common for both geese and ducks are 9 species (3 species of cestodes, 2 species of trematodes and 4 species of nematodes). The presence of such a large number of common species of parasites for both species of birds can be explained by keeping these birds under identical conditions with similar nutrition in the same farms. The percentage of helminth infection of geese and ducks in general for the Nakhchivan AR is 46.5%. Separately, the percentage of infection in the AR in geese is 45.1%, and in ducks 48.0%. The largest number of species of parasites by regions was recorded: Babek – 12 species, Sharur – 9 species and Kengerli – 8 species. Of the 14 species of helminths recorded on the territory of the Nakhchivan Autonomous Republic, three species (G. dispar, A. anseris, T. tenius) were recorded in all 7 regions with high prevalence and intensity of infection. The finding of these all 3 species of nematodes in different regions differing from each other in ecological conditions and their widespread distribution in these hosts can be explained by the fact that they have a simple cycle of development, and most importantly, that all of them are specific parasites of domestic waterfowl.